DIPG-32. Paediatric histone-mutant diffuse midline glioma: real world outcomes from a low-middle income country (LMIC) setting. (3rd June 2022) - Gupta, Tejpal; Chatterjee, Abhishek; Dasgupta, Archya; Mangaj, Akshay; Epari, Sridhar; Sahay, Ayushi; Choudhari, Amit; Moiyadi, Aliasgar; Shetty, Prakash; Chinnaswamy, Girish
Abstract: BACKGROUND: Histone-mutant diffuse midline glioma (H3K27M) is a distinct high-grade central nervous system (CNS) tumor arising in the midline structures of the brain and/or spinal cord in children and young adults with dismal clinical outcomes. Real world data on this entity, particularly from the low-middle income countries (LMICs) is lacking. We report outcomes of pediatric histone-mutant diffuse midline gliomas treated between 2014-2021 at our comprehensive cancer centre in India. METHODS: Children (<16 years) with biopsy-proven diffuse midline glioma demonstrating histone mutation (H3K27M) on gene expression profiling were identified through electronic search of neuro-pathology database. Clinico-demographic characteristics, histo-molecular features, treatment details, and survival outcomes were retrieved retrospectively from institutional records. All children had undergone biopsy and occasionally debulking surgery prior to definitive radiotherapy (RT). Upfront temozolomide (TMZ) either concurrent and/or adjuvant was at the discretion of treating oncologist. Progression-free survival (PFS) and overall survival (OS) were calculated using Kaplan-Meier methods and expressed as point estimates with 95% confidence interval (CI). RESULTS: Median age of the study cohort (N=51) was 11 years (inter-quartile range 6-14 years) with no gender predilection. Metastatic disease (leptomeningeal dissemination, sub-ependymal spread, or distant brain involvement) was seen at presentation in 7 (13.7%) patients and at first progression after definitive RT in 10 (19.6%) patients. At a median follow up of 10.3 months, 1-year Kaplan-Meier estimates of PFS and OS were 21.5% (95%CI: 12.2-37.9%) and 45.6% (33.1-62%) yielding median PFS and OS of 7.8 months (95%CI: 5.6-11 months) and 11.3 months (95%CI: 9.4-14.9 months) respectively. CONCLUSIONS: We report aggressive biological course and dismal outcomes in pediatric histone-mutant diffuse midline gliomas (H3K27M) treated in a LMIC setting. High incidence of metastatic CNS failure in our cohort suggests a potential role for testing neuraxial irradiation and aggressive systemic therapy to improve survival.